2000
DOI: 10.1161/01.atv.20.11.2483
|View full text |Cite
|
Sign up to set email alerts
|

P-Selectin–Dependent Inhibition of Thrombosis During Venous Stasis

Abstract: Abstract-Leukocyte adhesion, transendothelial migration, and stasis are important components in the pathogenesis of deep vein thrombosis. Anesthetized cats were treated with saline, a recombinant soluble form of P-selectin glycoprotein ligand-1 (rPSGL-Ig), or an E-and L-selectin antibody (EL-246) before exposure and occlusion of a jugular vein. After 2 or 6 hours of occlusion, jugular veins were perfused with buffer, fixed, and prepared for scanning electron microscopy. In cats receiving saline, 2 and 6 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 40 publications
3
49
0
1
Order By: Relevance
“…Although endothelial disruption is characteristic, it is often less extensive than that which triggers arterial thrombosis. 49 Additionally, leukocyte adhesion and transmigration have been demonstrated as early events in the initiation of venous thrombosis. 49,50 Thus, it has been proposed that circulating TF, perhaps derived from leukocytes, could be a key determinant of fibrin generation in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although endothelial disruption is characteristic, it is often less extensive than that which triggers arterial thrombosis. 49 Additionally, leukocyte adhesion and transmigration have been demonstrated as early events in the initiation of venous thrombosis. 49,50 Thus, it has been proposed that circulating TF, perhaps derived from leukocytes, could be a key determinant of fibrin generation in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…49 Additionally, leukocyte adhesion and transmigration have been demonstrated as early events in the initiation of venous thrombosis. 49,50 Thus, it has been proposed that circulating TF, perhaps derived from leukocytes, could be a key determinant of fibrin generation in this setting. 38,51 Interestingly, a recent study demonstrated that inhibition of TF significantly reduced fibrin accumulation on a collagen-coated thread implanted into a rabbit vein.…”
Section: Discussionmentioning
confidence: 99%
“…This process is dependent upon selectins, including P-selectin [14,15]. Genetic deficiency or pharmacological inhibition of P-selectin reduces thrombus formation across species [10,15,16]. P-selectin is released from Weibel-Palade bodies following endothelial activation [17,18].…”
Section: Dissecting the Early Phase Of Venous Thrombus Formationmentioning
confidence: 99%
“…One consequence is the inhibition of the interaction between P-selectin and its receptor, which occurs on different cell types, including platelets and leukocytes. Inhibiting the interaction between P-selectin and PSGL-1 with P-selectin antagonists (recombinant soluble PSGL-immunoglobulin), intravenously administered soluble ligands, or an orally administered nonprotein inhibitor (PSI-697) markedly attenuated the prothrombotic effect in a mouse model (13)(14)(15)(16)(17). Statin medication has recently been reported to reduce sP-selectin concentrations significantly (38 -40 ), and sP-selectin concentration was inversely correlated with the progression of coronary heart disease (38 ).…”
Section: /97mentioning
confidence: 99%